2013
DOI: 10.1186/1471-2164-14-636
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed in the sex pheromone gland of the black cutworm Agrotis ipsilon with putative roles in sex pheromone biosynthesis and transport

Abstract: BackgroundOne of the challenges in insect chemical ecology is to understand how insect pheromones are synthesised, detected and degraded. Genome wide survey by comparative sequencing and gene specific expression profiling provide rich resources for this challenge. A. ipsilon is a destructive pest of many crops and further characterization of the genes involved in pheromone biosynthesis and transport could offer potential targets for disruption of their chemical communication and for crop protection.ResultsHere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
83
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 83 publications
16
83
2
Order By: Relevance
“…Rodriguez et al reported that 95 % tetradecyl alcohol can be converted to tetradecyl acetate by ATF1 in strain AL1050 with a title 137 mg/L after 48 h. However, GC/MS analysis of extracts from the strain of our study revealed that a large number of fatty alcohols failed to be effectively converted to FAAEs, suggesting that further optimization of ATF1 expression level or identifying a better alcohol acetyltransferase to replace ATF1 in the future is a promising strategy for enhancing FAAE production in genetically engineered microorganisms. Given the accumulated knowledge about alcohol acetyltransferase (Gu et al 2013), it is believed that high productivity of FAAE production can be achieved through this novel pathway by further strain engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez et al reported that 95 % tetradecyl alcohol can be converted to tetradecyl acetate by ATF1 in strain AL1050 with a title 137 mg/L after 48 h. However, GC/MS analysis of extracts from the strain of our study revealed that a large number of fatty alcohols failed to be effectively converted to FAAEs, suggesting that further optimization of ATF1 expression level or identifying a better alcohol acetyltransferase to replace ATF1 in the future is a promising strategy for enhancing FAAE production in genetically engineered microorganisms. Given the accumulated knowledge about alcohol acetyltransferase (Gu et al 2013), it is believed that high productivity of FAAE production can be achieved through this novel pathway by further strain engineering.…”
Section: Discussionmentioning
confidence: 99%
“…mapped to phylogeny [253][254][255]. Detailed transcriptomic data of 1086 pheromone glands are available for several species [256][257][258][259]. …”
Section: Cytochrome P450smentioning
confidence: 99%
“…For instance, a collection 246 of five synergistic components secreted from the queen mandible 247 (collectively named the queen mandibular pheromone, QMP; 254 are also altered by queen pheromone activity. The chemical com- 255 plexity of the queen pheromone provides functional redundancy 256 and lowers the possibility of workers becoming desensitized to 257 individual components. 258 …”
mentioning
confidence: 99%
“…Although moth FARs usually exhibit a broad substrate preference [77,89,111,120,122,123], some of them display specificity to unsaturated substrates with a double bond in either the E or Z configuration [119], a particular chain length and double bond position [120], or a system of conjugated double bonds [118]. Given the multiple FAR paralogs generally present in insect genomes [13,14,16,17,111,124] and limited knowledge of their properties, there is a demand to perform functional characterization of these biologically and biotechnologically relevant enzymes. FARs from insects other than moths are virtually unexplored.…”
Section: Far Propertiesmentioning
confidence: 99%
“…The diversification of the pheromone-biosynthetic enzymes likely has been driven by evolutionarily imposed requirements on sex pheromone signal specificity [11,12]. A broad spectrum of insect pheromone-biosynthetic enzymes has already been functionally characterized, and transcriptomic sequencing (RNA-seq) of pheromone glands using next-generation sequencing has identified new candidates for characterization [13][14][15][16][17][18][19]. RNA-seq of other insect glands and tissues may open the door to the discovery of many additional enzymes with remarkable biosynthetic capabilities [8].…”
Section: Introductionmentioning
confidence: 99%